Customer based brand equity: evidence from the hotel industry - Kayaman, Rüçhan; Araslı, Hüseyin (Emerald Group Publishing, 2007)
The paper aims to explore interrelations of the four brand equity components; brand awareness, brand loyalty, perceived quality and brand image in hotel industry and improve the conceptualization of customer-based hotel brand equity. The paper is based on the recommendations of previous studies, the scale constructed to measure consumer-based brand equity included brand awareness, brand loyalty, perceived quality and brand image. The present study used a sample of 345 actual customers from 11 different countries whose accommodation in North Cyprus hotels was used to test the relations of the proposed model Path analysis. The findings in this paper support the three-dimensional model of customer-based brand equity in hotel industry. Brand awareness dimension was not found significant in the tested model for hotels. The present study contributes to the understanding of customer-based brand equity measurement by examining the dimensionality of this construct. Further research in this paper should attempt to examine brand equity across many different hotel categories. This will give the opportunity to make comparisons between different hotels' products and this concept. Furthermore, intra relationship of customer based-brand equity components on the hotel performance needs to be investigated. The paper shows that hotel managers and executives should try to influence; perceived quality, brand loyalty, brand image and brand awareness in their organizations and design their service delivery process by considering relations between customer based brand equity components. The principal contribution of the paper is that it provides important insights into the development and measurement of customer based hotel brand equity scale and limited hotel brand equity literature.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Brand equity, Brand image, Hotels, Cyprus; Brand loyalty, Turkey, Brand awareness; Customer relations, Quality of service, Studies, Hotels & motels